Assessing the impact of the introduction of an electronic hospital discharge system on the completeness and timeliness of discharge communication: a before and after study - Mehta, Rajnikant; Baxendale, Bryn; Roth, Katie; Caswell, Victoria; Le Jeune, Ivan; Hawkins, Jack; Zedan, Haya Saud; Avery, Anthony J. (BIOMED, 2017)
Background: